Enhancing the Role of Civil Society Organizations in the Fight against Corruption in Nigeria - Surajo Yahaya Muhammad (Journal of Social and Development Sciences, 2017)
Abstract: To ensure the attainment of good governance and sustainable development, corruption and its scourge must be combated. In Nigeria, the state has had series of anti-corruption measures by successive administrations in its 55 years of existence as an independent entity. While such measures appeared to have been well packaged, however, absence of political will and inability of the state to regard civil society organizations as important partner in the anti corruption has retarded the country’s ability to get rid of the menace of corruption, hence the inability of Nigerian state to provide effective and efficient services to its teeming populace. Being a partner in the development process of modern state, and in order to effectively enhance their roles in the fight against corruption, the paper proper ways upon which civil society groups can organize themselves and work with the state to get rid of corruption in the country.Keywords: Civil Society, Corruption, Democracy, Democratization, State